Patient with an autosomal-recessive MBTPS1-linked phenotype and clinical features of Silver-Russell syndrome - Meyer, Robert; Elbracht, Miriam; Opladen, Thomas; Eggermann, Thomas (American journal of medical genetics, 2020)
Pathogenic variants in the MBTPS1 gene encoding the Site 1 protease have been described so far only in one growth retarded patients with skeletal deformities, large ears, a triangular face reminiscent to Silver-Russell syndrome (SRS), and elevated blood lysosomal enzymes. We now report on the identification of a second adult patient homozygous for one of the two published pathogenic MBTPS1 variants (p.Asp365Gly) by Whole Exome Sequencing (WES), and a comparable phenotype. With this case, the association of pathogenic variants in MBTPS1 with a recognizable disorder could be confirmed, and the autosomal recessive inheritance is further established. As the variant was identified after a long diagnostic odyssey of the family, this example illustrates the need to apply WES in the diagnostic workup in case of growth retardation as early as possible. By compiling the clinical data of this new patient with those of the already reported patient, a better prognosis for future patients with MBTPS1 variants can be issued, and clinical management can be adjusted.
Gesehen am 19.02.2026